2021
DOI: 10.1007/s10549-021-06105-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of age, rurality and distance in predicting contralateral prophylactic mastectomy for breast cancer in a Midwestern state: a population-based study

Abstract: Background: There is substantial variability in the use of contralateral prophylactic mastectomy (CPM) in women with unilateral breast cancer across the United States. Iowa is one of several rural Midwestern states found to have the highest proportions of CPM nationally in women <45 years of age. We evaluated the role of rurality and travel distance as factors related to these surgical patterns. Methods: Women with unilateral breast cancer (2007-2017) were identi ed using Iowa Cancer Registry records. Patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 38 publications
(37 reference statements)
0
10
0
Order By: Relevance
“…The impact of breast cancer diagnosis and management on patients is not uniform across the country, as certain populations may face increased challenges in terms of awareness, education, socioeconomics, access to care, and culture. 1,8,14 This is especially pronounced in women from a rural population, [8][9][10] and deserves further investigation to identify the most impactful factors that affect breast reconstruction. A study published in 2019 demonstrated that in the state of Tennessee, lower income is associated with significantly worse health outcomes and life expectancy, reinforcing the importance of identifying and addressing specific social determinants of health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of breast cancer diagnosis and management on patients is not uniform across the country, as certain populations may face increased challenges in terms of awareness, education, socioeconomics, access to care, and culture. 1,8,14 This is especially pronounced in women from a rural population, [8][9][10] and deserves further investigation to identify the most impactful factors that affect breast reconstruction. A study published in 2019 demonstrated that in the state of Tennessee, lower income is associated with significantly worse health outcomes and life expectancy, reinforcing the importance of identifying and addressing specific social determinants of health.…”
Section: Discussionmentioning
confidence: 99%
“…8 Although academic programs have the highest rates of reconstruction, they may be located farthest from patients' residences, and older, non-White patients, with lower education level and higher out-of-pocket costs may be less likely to undergo reconstruction. 1,[4][5][6][7][9][10][11][12] Previous studies examining factors that impact reconstruction after mastectomy have focused on national or statewide databases. The aim of this study was to identify specific factors that may affect rates and type of breast reconstruction after mastectomy in a rural patient population compared with national trends.…”
Section: Introductionmentioning
confidence: 99%
“…These findings may represent lack of access to reconstruction in areas proximate to non-metro counties, or a lack of suitability or inclination for reconstruction in non-metro women who elect not to or are unable to travel farther. While we cannot determine from this dataset whether the distance traveled by the patient represents the distance to the nearest available treating facility, one study using Iowa Cancer Registry data found that rural women frequently traveled to large tertiary care centers for surgery, which were often not the nearest hospitals offering breast cancer surgery [23]. In that study, rural women traveling to large tertiary facilities were more likely to elect CPM and have reconstruction than metro women treated in similar facilities [23].…”
Section: Discussionmentioning
confidence: 97%
“…However, unexpectedly high proportions (42.8-48.5%) of CPM have been reported among women aged 20-44 with early-stage unilateral breast cancer who underwent surgery in Midwestern states that have a high proportion of rural residents. A study in Iowa, which had the second highest proportion of breast cancer patients electing CPM [22], identified the highest rates of CPM among rural-residing women under the age of 40 [23]. Rural patients often travel farther for many aspects of cancer treatment, which contributes to the lower rates of guideline concordant care in this population [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation